Enhancing Safety in U.S. Coal Mines Through a Rib Support Recommendation Tool - Alper Kirmaci; Dakshith Ruvin Wijesinghe; Dogukan Guner; Kutay E. Karadeniz; Cameron Mitchell; Taghi Sherizadeh (Geosciences)
Despite ongoing efforts to enhance coal rib stability, the underground coal mining sector continues to face incidents of rib failure, leading to injuries and fatalities. The development and validation of effective rib support systems are crucial for mitigating these risks. Unfortunately, a standardized design methodology that accommodates the diverse geological conditions of U.S. coal mines is missing. Current practices are often based on trial-and-error or outdated methods, yielding unreliable outcomes. This research aims to fill this gap by creating a comprehensive methodology for designing rib support systems suitable for U.S. underground mines. It encompasses in situ pull-out tests of coal rib bolts, numerical model validations, and parametric studies on variables affecting rib stability. A significant achievement of this study is the creation of the rib support recommendation tool (RSR), a user-friendly application that offers site-specific rib support advice. This tool leverages the results from parametric studies and improved Coal Pillar Rib Rating (CPRR) system values to recommend effective rib support. Validated by field data, the RSR tool promises to significantly improve mining safety and efficiency by providing a systematic and reliable method for rib support design, with ongoing efforts to further validate its effectiveness.